(untitled) (INTERNATIONAL JOURNAL OF RECENTLY SCIENTIFIC RESEARCHER’S THEORY, 2025)
This article analyzes advanced methods used in teaching the Kazakh language in general education schools based on modern educational requirements. The main focus is on the practical effectiveness of such methods as the communicative approach, CLIL technology, digital tools, and gamification. During the study, an increase in students’ interest and active participation in language learning was observed. The article also presents existing problems and recommendations for their elimination.